2011
DOI: 10.1246/cl.2011.341
|View full text |Cite
|
Sign up to set email alerts
|

Platinum Metals in the Catalytic Asymmetric Isomerization of Allylic Alcohols

Abstract: Past and recent advances in the metal-catalyzed asymmetric isomerization of allylic alcohols into carbonyl compounds are discussed in the present Highlight. Emphasis is placed on rhodium, ruthenium, and iridium; the only three metals that have proven successful to date for this most challenging transformation. Ç IntroductionThe metal-catalyzed asymmetric isomerization of primary and secondary allylic alcohols into the corresponding aldehydes and ketones®a reaction of both academic and industrial relevance®has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…Catalyst 2 was also efficient for the isomerization of a family of mono-and di-substituted allylic alcohols (see Scheme 4). As previously observed in this metal-catalyzed isomerization (90)(91)(92)(93)(94)(95)(96)(97), a strong dependence upon the substitution grade on the olefin was observed, thereby higher ruthenium charges (5-10 mol% Ru) and reaction time (8-24 h) were required to promote the isomerization of di-substituted allylic alcohols. Finally, the mentioned conditions allowed for the recycling of the catalytic system during 4 consecutive cycles, with no significant observation of loss of activity during the two first runs.…”
Section: Metal-catalyzed Isomerization Reactionssupporting
confidence: 76%
See 1 more Smart Citation
“…Catalyst 2 was also efficient for the isomerization of a family of mono-and di-substituted allylic alcohols (see Scheme 4). As previously observed in this metal-catalyzed isomerization (90)(91)(92)(93)(94)(95)(96)(97), a strong dependence upon the substitution grade on the olefin was observed, thereby higher ruthenium charges (5-10 mol% Ru) and reaction time (8-24 h) were required to promote the isomerization of di-substituted allylic alcohols. Finally, the mentioned conditions allowed for the recycling of the catalytic system during 4 consecutive cycles, with no significant observation of loss of activity during the two first runs.…”
Section: Metal-catalyzed Isomerization Reactionssupporting
confidence: 76%
“…Isomerization reactions are typical examples of atom economic processes in which no by-products are generated. Thus, the redox isomerization of readily accessible allylic alcohols catalyzed by transition-metal complexes is a useful and straightforward synthetic route to saturated carbonyl compounds, which are very important raw materials in organic synthesis (90)(91)(92)(93)(94)(95)(96)(97). In this sense, García-Álvarez et al described the unique example reported to date for the redox isomerization of allylic alcohols in DESs catalyzed by the Ru(IV)-complex [Ru(η 3 :η 3 -C 10 H 16 )Cl 2 (κ 1 -N-benzimidazole)] (2) (98).…”
Section: Metal-catalyzed Isomerization Reactionsmentioning
confidence: 99%
“…[14] Previous studies support that the formation of a-functionalized carbonyl compounds from allylic alcohols occurs through: 1) a transition-metal-catalyzed 1,3-hydrogen shift forming an enolate or an enol intermediate, and 2) subsequent nucleophilic attack on the electrophile (Scheme 4). [6][7][8][9] In a cross-over experiment using deuterium-labeled [D 1 ]-2 f, we have confirmed that the isomerization follows an intramolecular 1,3-hydrogen shift (Scheme 5 and the Supporting Information). [7b, 8] Although this result is consistent with the intermediacy of enol(ate)s, the details of the mechanism, and in particular of the C À Cl bond formation step, remain to be elucidated.…”
supporting
confidence: 52%
“…A considerable advantage of using allylic alcohols as enol equivalents [6,7] is that the new bond (to the electrophile) is formed exclusively at the alkenylic carbon atom of the allylic alcohol [RCH(OH) À CH = CHR; Scheme 1b]. This type of transformation has almost exclusively been investigated using carbon electrophiles (e.g.…”
mentioning
confidence: 99%
“…[69][70][71][72] The process involves the spontaneous tautomerization of the intermediate enol formed during the C=C bond migration. In this context, the magnetic nanoparticles 1, decorated on the surface with a RAPTA-type complex (see Scheme 8.1), have proven to be an efficient catalytic system for the redox isomerization of allylic alcohols (Scheme 8.5).…”
Section: Olefin Isomerization Processesmentioning
confidence: 99%